A Specific Glycogen Mobilization Strategy Enables Rapid Awakening of Dormant Cyanobacteria from Chlorosis. Issue 2 (27th April 2018) - Doello, Sofia; Klotz, Alexander; Makowka, Alexander; Gutekunst, Kirstin; Forchhammer, Karl
Abstract : Rapid reanimation of a photosynthetic bacterium following nitrogen starvation is facilitated by anticipation and requires two parallel routes of glycogen catabolism and a particular glycogen phosphorylase paralog. Abstract: Many organisms survive stressful conditions via entry into a dormant state that can be rapidly exited when the stressor disappears; this ability provides a strong selective advantage. In the cyanobacterium Synechocystis sp. PCC 6803, the exit from nitrogen chlorosis takes less than 48 h and is enabled by the impressive metabolic flexibility of these cyanobacteria, which pass through heterotrophic and mixotrophic phases before reentering photoautotrophic growth. Switching between these states requires delicate coordination of carbohydrate oxidation, CO2 fixation, and photosynthesis. Here, we investigated the contribution of the different carbon catabolic routes by assessing mutants of these pathways during nitrogen chlorosis and resuscitation. The addition of nitrate to nitrogen-starved cells rapidly starts the awakening program. Metabolism switches from maintenance metabolism, characterized by residual photosynthesis and low cellular ATP levels, to an initial heterotrophic phase, characterized by respiration and an immediate increase in ATP levels. This respiration relies on glycogen breakdown catalyzed by the glycogen phosphorylase GlgP2. In the following transient mixotrophic phase, photosynthesis and CO2 fixation restart and glycogen is consumed. During the mixotrophic phase, parallel operation of the oxidative pentose phosphate cycle and the Entner-Doudoroff pathway is required for resuscitation to proceed; the glycolytic route via the Embden-Meyerhof-Parnas pathway has minor importance. Our data suggest that, during resuscitation, only the Entner-Doudoroff and oxidative pentose phosphate pathways supply the metabolic intermediates necessary for the anabolic reactions required to reconstitute a vegetative cell. Intriguingly, the key enzymes for glycogen catabolism are already expressed during the preceding chlorotic phase, in apparent preparation for rapid resuscitation.